Pemanfaatan Colopogonium mucunoides sebagai Pupuk Hijau terhadap Pertumbuhan dan Produksi Tanaman Tomat di Media Tailing Pasir Pasca Penambangan Timah: Pemanfaatan Colopogonium mucunoides sebagai Pupuk Hijau terhadap Pertumbuhan dan Produksi Tanaman Tomat di Media Tailing Pasir Pasca Penambangan Timah - Juanda Ramadhika; Ratna Santi; Rion Apriyadi (Universitas Bangka Belitung, 2018)
Green manure (Colopogonium mucunoides) is one type of organic fertilizer derived from Leguminosae plants. Green manure has the potential to increase soil nutrients, especially N (nitrogen). Utilization of green manure on post-tin mining soil to improve soil organic matter and improve the physical, chemical and biological properties of tailing sand. The aim of this research is to find the growth and production response of tomatoes with the addition of Colopogonium mucunoides as green manure on post-tin mining media. The research had been conducted on March until June 2017 in The Experimental And Research Garden, Faculty of Agriculture, Fishery, and Biology, University of Bangka Belitung. This research used a Completely Randomized design single factor. The treatment level was: CM0 = 0 g/plant, CM1 = 200g/plant, CM2 = 400g/plant, CM3 600 g/plant, CM4 = 800 g/plant, CM5 = 1000g/plant. Each treatment was replicated 3 times to obtain 18 experiment units. Each experiment unit consists of 4 samples. The result of the experiment showed that the tomato plant with green manure (Colopogonium mucunoides) provide various responses to the growth and production of tomato plants on post-tin mining media. Utilization of Colopogonium mucunoides as green manure has no significant effect on all observed parameters.